Transcription factors Fli1 and EKLF in the differentiation of megakaryocytic and erythroid progenitor in 5q- syndrome and in Diamond-Blackfan anemia - Neuwirtová, Radana; Fuchs, Ota; Holická, Monika; Vostrý, Martin; Kostečka, Arnošt; Hájková, Hana; Jonášová, Anna; Čermák, Jaroslav; Čmejla, Radek; Pospíšilová, Dagmar; Beličková, Monika; Šišková, Magda; et al. (Annals of hematology, 2013)
Friend leukemia virus integration 1 (Fli1) and erythroid Krüppel-like factor (EKLF) participate under experimental conditions in the differentiation of megakaryocytic and erythroid progenitor in cooperation with other transcription factors, cytokines, cytokine receptors, and microRNAs. Defective erythropoiesis with refractory anemia and effective megakaryopoiesis with normal or increased platelet count is typical for 5q- syndrome. We decided to evaluate the roles of EKLF and Fli1 in the pathogenesis of this syndrome and of another ribosomopathy, Diamond-Blackfan anemia (DBA). Fli1 and EKLF mRNA levels were examined in mononuclear blood and bone marrow cells from patients with 5q- syndrome, low-risk MDS patients with normal chromosome 5, DBA patients, and healthy controls. In 5q- syndrome, high Fli1 mRNA levels in the blood and bone marrow mononuclear cells were found. In DBA, Fli1 expression did not differ from the controls. EKLF mRNA level was significantly decreased in the blood and bone marrow of 5q- syndrome and in all DBA patients. We propose that the elevated Fli1 in 5q- syndrome protects megakaryocytic cells from ribosomal stress contrary to erythroid cells and contributes to effective though dysplastic megakaryopoiesis.
Keywords: Proto-Oncogene Protein c-fli-1; Chromosome Deletion; Real-Time Polymerase Chain Reaction; buňky kostní dřeně; CpG Islands; lidé; mladiství; Adult; Chromosomes, Human, Pair 5; leukocyty mononukleární; transkripční faktory Krüppel-like; Ribosomal Proteins; ribozomální proteiny; Female; dítě; Thrombopoiesis; messenger RNA; RNA, Messenger; protoonkogenní protein c-fli-1; Myelodysplastic Syndromes; erytropoéza; Adolescent; Humans; CpG ostrůvky; chromozomální delece; lidské chromozomy, pár 5; Erythropoiesis; genetická transkripce; mužské pohlaví; mladý dospělý; Kruppel-Like Transcription Factors; ženské pohlaví; Anemia, Macrocytic; Young Adult; Bone Marrow Cells; Male; Leukocytes, Mononuclear; kvantitativní polymerázová řetězová reakce; myelodysplastické syndromy; Child; dospělí; Anemia, Diamond-Blackfan; Transcription, Genetic; makrocytární anemie; trombopoéza; Diamondova-Blackfanova anemie